The alleviating specific phobias in children trial: Challenges and solutions to implementing a randomized controlled trial in clinical services - Tindall, Lucy; Scott, Alexander J.; Biggs, Katie; Hayward, Emily; Wilson, Jon; Cooper, Cindy; Hargate, Rebecca; Wright, Barry; Gega, Lina (Frontiers in Child and Adolescent Psychiatry, 2022)
In 2015, The Alleviating Specific Phobias Experienced by Children Trial (ASPECT) was commissioned by the National Institute for Health and Care Research (NIHR) to compare the clinical and cost-effectiveness of multi-session Cognitive Behavioural Therapy (CBT) for specific phobias in children and young people (CYP) (aged 7 to 16), with a briefer variant called One Session Treatment (OST). From 2016 to 2020, ASPECT recruited n=274 CYP with specific phobias and their families from across England, including 26 Child and Adolescent Mental Health Services (CAMHS) centres, 3 voluntary sector centres and one University-based wellbeing service. Whilst the trial successfully reached its recruitment target, the challenges experienced in its delivery highlight the difficulties of embedding child and adolescent research into clinical settings and routine practice. Using ASPECT as a case in point, this paper explores these challenges and provides important insights and considerations of potential benefit to others conducting research within the field of child and adolescent mental health.